PADRÕES DE CONVERGÊNCIA E CONVERGÊNCIA: UMA ANÁLISE DA INDÚSTRIA BRASILEIRA - Almeida, Manoel Bosco de; Carvalho Júnior, José Raimundo de Araújo; França, João Mário Santos de (Revista Econômica do Nordeste, 1997)
Acervo histórico